2022
DOI: 10.1016/j.theriogenology.2021.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol effectively improves the quality of pig sperm at 17 °C

Abstract: Background: Arti cial insemination technology is the production technology used in more than 99% of the world's pig farms. As the frozen sperm damage is very serious, the preservation of pig sperm is mainly carried out at 17°C. However, the accumulation of a large amount of reactive oxygen species (ROS) during the preservation process is the main reason for the deterioration of sperm quality. In our research, by adding different concentrations of hydroxytyrosol to the diluent during the storage of pig sperm at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In this same species, Arando et al [48] observed that supplementation of semen with HT improves LPO values of frozen-thawed samples as well as in the case of DHPG and the mixture of both. Similarly, Li et al [51] have reported that the addition of 120 µmol/L of HT during boar semen storage at 17 • C has a positive effect on semen quality.…”
Section: Discussionmentioning
confidence: 82%
“…In this same species, Arando et al [48] observed that supplementation of semen with HT improves LPO values of frozen-thawed samples as well as in the case of DHPG and the mixture of both. Similarly, Li et al [51] have reported that the addition of 120 µmol/L of HT during boar semen storage at 17 • C has a positive effect on semen quality.…”
Section: Discussionmentioning
confidence: 82%
“…Hydroxytyrosol showed antioxidant properties by scavenging ROS, reducing the accumulation of ROS, and promoting the expression of antioxidant enzymes via activating nuclear factor E2-related factor 2 (Nrf2) signaling [ 31 ]. Moreover, hydroxytyrosol enhanced the activity of antioxidant enzymes (CAT, T-AOC, SOD, and GSH-PX), which led to reduced lipid peroxidation (MDA) in pig semen stored at 17°C [ 32 ] and catalyzed the decomposition of hydrogen peroxide (H 2 O 2 ) in postweaning piglets [ 33 ]. Furthermore, Kedechi et al [ 34 ] reported that the addition of hydroxytyrosol reduced sperm DNA oxidation in human semen.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to previous studies, improving semen quality positively affects their in vitro and in vivo fertilization ability or reproductive performance. For example, the addition of hydroxytyrosol to a dilution of boar semen improved the artificial insemination efficiency by improving the sperm quality [57]. Moreover, the addition of tretinoin enhanced IVF parameters and spermoocyte binding by improving the boar sperm quality, increasing the cleavage and blastocyst rates [9].…”
Section: Discussionmentioning
confidence: 99%